Intraspecific olive diversity assessed with AFLP - Sanz-Cortés, F.; Parfitt, Dan E.; Romero, Carlos; Struss, D.; Llácer, Gerardo; Badenes, María L. (Wiley Online Library, 2020)
Amplified fragment length polymorphism (AFLP) was used to study diversity within and among Spanish olive varieties. A high degree of diversity was found among the varieties present in each growing region. Olive oil production and quality relies on appropriate cultivar selection as well as good orchard management. Production based only on a few superior cultivars would result in improved yield, oil quality, and production management. Amplified fragment length polymorphism were evaluated as a tool to identify the intraspecific and intravarietal diversity of olive. Amplified fragment length polymorphism analysis of 38 accessions belonging to 10 cultivars using six primer combinations produced 106 polymorphic bands. Results were analyzed for similarity among accessions via unweighted pair‐group means cluster analysis, resulting in 10 clusters corresponding to named variety designations. Similarity among varieties ranged from 0.60 to 0.72. Diversity within varieties was identified. Similarity within named varieties (accessions with the same varietal name) ranged from 0.75 to 0.96. Differences in several markers were found among 34 accessions. Intravarietal diversity was shown to exist within the Spanish olive varieties grown in the region surrounding Valencia.